Literature Study of the Application of Skimming Techniques to Improve Speed ​​Reading Ability in Indonesian Language Lessons for Class V Elementary School Students: Literature Study of the Application of Skimming Techniques to Improve Speed ​​Reading Ability in Indonesian Language Lessons for Class V Elementary School Students - Rufaida, Dien; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to describe the process of skimming techniques for elementary school students to improve their reading skills. This study uses a literature study approach using systematic literature review (SLR) method. The subject is a journal derived from google scholar with research limitations of elementary school students that have been analyzed by researchers. Based on the results of Eve's research that there is an improvement in reading skills in Indonesian lessons for students. This can be seen from the first and second cycles of active students, educators as well as student learning outcomes. The first cycle of the number of grades for the observation of students' activeness, the score obtained by 62.5% with sufficient predicate. While in the second cycle the number of scores obtained on the activeness of students learning scored 87.5% with a good predicate and very good. According to the results of muhtar research that after the analysis of t- test paired obtained that there is an influence of the application of skimming techniques to the reading ability of students. According to the results of fitria research based on the results of the average ability to read quickly by skimming on a sample of 16 students, which is adjusted to the percentage interval scale of five to know the level of ability of students. After adjusting to the five-scale score interval, it is known to obtain a score of 95.25%, therefore this score falls into the category Excellent. It can be proven that the ability of students at the time of quick reading by using skimming techniques is included in the category of very good during the test of quick reading and in understanding the content of the text readingFrom the results of analyzing research that has been done previously conducted by Hawa, Muhtar, and Fitria that skimming techniques can help students' ability to read quickly in Indonesian lessons.